Optical Spectral Variations of a Large Sample of Fermi Blazars - Zhang, Bing-Kai; Zhao, Xiao-Yun; Wu, Qi (The Astrophysical journal. Supplement series, 2022)
We have investigated the optical spectral behavior of a large sample of Fermi blazars (40 flat-spectrum radio quasars (FSRQs) and 13 BL Lacertae objects (BL Lacs)), and found two new universal optical spectral behaviors. In the low state the optical spectrum gradually becomes softer (steeper) or harder (flatter), but more and more slowly as the brightness increases, and then tends to stabilize in the high state. These are briefly named the redder-stable-when-brighter (RSWB) and bluer-stable-when-brighter (BSWB) behaviors, respectively. Thirty-four FSRQs and 7 BL Lacs exhibit clear RSWB behavior, and 2 FSRQs and 5 BL Lacs show distinct BSWB behavior, which means that FSRQs favor more RSWB than BSWB behavior, while BL Lacs have no clear preference between both behaviors. We have put forward a unified nonlinear formula to quantitatively characterize the optical spectral behaviors of FSRQs and BL Lacs, which can fit both kinds of behaviors very well. We argue that the RSWB and BSWB behaviors originate from the same mechanism, and that they are the universal optical spectral behaviors for blazars. The frequently observed redder-when-brighter and bluer-when-brighter trends can be considered to be the approximations of the RSWB and BSWB behaviors, respectively. The rarely observed stable-when-brighter trend can also be viewed as an approximation or a special case of the RSWB or BSWB behaviors. We have developed a model with two constant-spectral-index components, which cannot only explain the two kinds of optical spectral behaviors well, but also successfully interpret the differential behaviors between FSRQs and BL Lacs.